Evaluation of surface roughness and Candida albicans attachment on light cured and heat cured acrylic denture base resin using Corega, Fittydent and Lacalut denture cleansers (Mustansiria Dental Journal, 2019)
Background: Denture cleansers are the most widely used by the patients to maintain clean denture as the presence of Candida albicans on the surfaces of denture-base acrylic resins is strongly related to the development of oral stomatitis but the cleansers may have harmful effect on some properties of the denture. So the aim of this study is to evaluate and compare the effect of different denture cleansers on the surface roughness and adherence of the Candida albicans on the light and heat cured acrylic resin materials.Materials and methods: Eighty specimens were made from two different denture base materials for each test.  Forty specimens were made of light cured acrylic and forty specimens were made of heat cured acrylic resin. Each material group was subdivided into four subgroups according to the type of the denture cleansers and the distilled water that was used as control group. Antimicrobial activity and the surface roughness test were measured for each specimen to show the effect of each denture cleansers on surface of the denture base materials.Results: The results showed that there were highly significant differences in the antimicrobial activity before and after the use of denture cleansers while there were no significant differences in surface roughness between before and after immersion in the denture cleansers for both acrylic specimens. While the surface roughness and the Candida albicans attachment to light cured acrylic was significantly higher than that of heat cured acrylic specimens.Conclusion: It was concluded that the Candida albicans attachment was effected by the immersion in the denture cleansers while the roughness of acrylic materials was not affected by immersion in denture cleansers as well as it was found that the Candida albicans attachment and the surface roughness of the light cured  was  higher than the heat cured acrylic denture base.